Gurinder Chadha’s Bride and Prejudice: A Transnational Journey Through Time and Space - Elena Oliete-Aldea (International Journal of English Studies (IJES), 2012)
At the beginning of the 21st century, the processes of globalization have propelled intense cultural contacts between formerly cohesive communities resulting in both homogenizing and hybridizing socio-cultural changes (Robertson, 1995: 27); these changes, however, go hand in hand with a “global fear” of a potentially threatening “other”, which fuel people to take defensive actions that re-create “protective” prejudices and boundaries (Bauman, 2006: 97). As culturally hybrid products, transnational films not only transcend the limits of cinematic genres but cultural boundaries based on prejudice and uneven power relations. Chadha’s transnational movie Bride and Prejudice (2004) includes elements of Hollywood, Bollywood and British cinematic traditions to create a hybrid transnational film that metaphorically represents the re-emergence of past prejudices in contemporary encounters of Eastern and Western cultures. Following a cultural studies methodological approach, this article intends to analyze the competing meanings and interpretations the film offers when set against its globalized cultural background. En los albores del siglo XXI, los procesos de la globalización han intensificado intercambios culturales entre comunidades hasta entonces cerradas, dando lugar a cambios sociales conducentes a la homogeneidad o a la hibridación de las culturas (Robertson, 1995: 27); esta situación también suele ir acompañada del “miedo global” a un “otro” potencialmente amenazador, lo cual provoca acciones defensivas que recrean prejuicios y fronteras “protectoras” (Bauman, 2006: 97). Como producto cultural híbrido, el cine transnacional no sólo transciende los límites de los géneros cinematográficos si no que también traspasa los de las identidades culturales basadas en prejuicios y relaciones de poder desiguales. La película de Gurinder Chadha Bodas y Prejuicios (2004) incluye ingredientes de tradiciones cinematográficas de Hollywood, Bollywood, y del Reino Unido para crear un film transnacional sobre los prejuicios que todavía prevalecen en los encuentros entre Oriente y Occidente. Siguiendo un enfoque metodológico cultural de carácter interdisciplinar, en este artículo se pretende analizar los diversos significados que esta película ofrece cuando se estudia dentro del marco de la globalización cultural.